Актуальні аспекти біології тварин, ветеринарної медицини та ветеринарно-санітарної експертизи - (:unkn) unknown (Дніпровський ДАЕУ, 2024)
Викладено матеріали ІХ Міжнародної науково-практичної конференції викладачів і здобувачів вищої освіти «Актуальні аспекти біології тварин, ветеринарної медицини та ветеринарно-санітарної експертизи» з найбільш важливих напрямків сучасної ветеринарної медицини та ветеринарно-санітарної експертизи, яка відбулася 28-29 травня 2024 р. Materials are outlined ІX International Scientific and Рractical Conference of Teachers and Applicants for higher education “Actual aspects of animal biology, veterinary medicine and veterinary - sanitary examination” the most important directions of modern veterinary medicine and veterinary-sanitary examination, May 28-29, 2024.
Actual aspects of animal biology, veterinary medicine and veterinary-sanitary examination
Keywords: коти; cats; ветеринарна медицина; veterinary medicine; ветеринарно-санітарна експертиза; veterinary and sanitary examination; тваринництво; animal husbandry; собаки; dogs